The Impact of Educational Technology Advancements on Efficiency and Professional Teacher Training in Sidrap Regency - Syamsu T; Muhammad Sabri; Erlita Erlita; Sam Hermansyah; Dr.S.H.Sheik Mohamed (Universitas Muhammadiyah Enrekang, 2024)
This study examines the impact of educational technology advancements on the efficiency and effectiveness of professional teacher training programs in Sidrap Regency. The integration of technology in education has created opportunities for flexible, accessible, and innovative learning, particularly in improving teacher competencies. Through the use of online platforms, digital tools, and multimedia resources, educational technology supports teachers in enhancing their skills and pedagogical approaches.Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis with teachers and training coordinators. The findings indicate that while educational technology improves efficiency by offering flexible learning and collaborative opportunities, challenges persist, such as limited digital literacy, insufficient infrastructure, and inconsistent internet access in rural areas. Despite these barriers, teachers recognize the benefits of technology in making professional training more effective and engaging. The study concludes that targeted interventions, including digital literacy training, infrastructure improvements, and increased support for technology adoption, are necessary to maximize the impact of educational technology. These findings provide valuable insights for policymakers and educational institutions to enhance teacher training programs, ensuring they meet the demands of modern education systems.